2021
DOI: 10.1371/journal.pone.0246932
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and diversity of mosquitoes and Oropouche-like virus infection rates in an Amazonian rural settlement

Abstract: Mosquito diversity and disease transmission are influenced by landscape modifications, i.e., vectors and pathogens previously found only in forests are now found close to human environments due to anthropic changes. This study determined the diversity and distribution of mosquitoes in forest environments in order to analyze the potential vectors of Amazonian forest arboviruses. Mosquitoes were collected by 1) vertical stratification from forest canopy and ground areas using Hooper Pugedo (HP) light traps and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 51 publications
3
8
1
Order By: Relevance
“…This was also reflected in the results of the principal components analysis. Other studies 44 46 have shown similar changes in community composition with increasing height above the forest floor and found that species richness and mosquito abundance are generally higher at ground level than at the heights sampled in this study. We also found species richness to be greatest at 0 m, although overall abundance was similar between 0 and 9 m. The latter finding may be explained by our sampling methods which limited collections to one mosquito per minute, potentially underestimating abundance at ground level.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This was also reflected in the results of the principal components analysis. Other studies 44 46 have shown similar changes in community composition with increasing height above the forest floor and found that species richness and mosquito abundance are generally higher at ground level than at the heights sampled in this study. We also found species richness to be greatest at 0 m, although overall abundance was similar between 0 and 9 m. The latter finding may be explained by our sampling methods which limited collections to one mosquito per minute, potentially underestimating abundance at ground level.…”
Section: Discussionsupporting
confidence: 79%
“…albigenu which were frequently caught at each height. While Psorophora species are known to be predominantly ground dwelling, they are often collected in the forest canopy 46 , 47 . In our study, the high relative abundance of both Ps.…”
Section: Discussionmentioning
confidence: 99%
“…However, at high densities, it can behave as an opportunistic species, and depending on the availability of vertebrate hosts, it can play a role in malaria transmission. In the present study, these species showed attractiveness to humans, as observed in other studies 29 , 30 . The evidence that those two species can bite humans in addition to the susceptibility to P. vivax and the capacity to develop sporozoites indicates that they must be important for maintenance of malaria transmission cycles.…”
Section: Discussionsupporting
confidence: 92%
“…Eclectic mosquitoes can serve as bridge vectors of pathogens from canopy-dwelling hosts to ground-dwelling hosts and vice versa [ 88 94 ] Seasonal distribution Accentuated (abrupt population peaks); moderate (no abrupt peaks) Populations increase abruptly in response to certain environmental events (e.g., rain, temperature), which increases vectorial capacity and determines the most favorable periods for transmission of pathogens [ 50 , 60 , 72 , 78 , 87 , 92 , 95 99 ] Environment Forest interior; forest edge; peri-urban; urban Ability to withstand different degrees of environmental impact and ecological impoverishment. Also reflects anthropophily and interspecific competition [ 46 , 60 , 83 , 94 , 98 , 100 ] Epidemiological importance YFV natural infection; YFV transmission in experimental infections; YFV primary vector; YFV secondary or local vector Indicates the accumulated evidence for vector competence and vectorial capacity of the species [ 16 , 43 , 44 , 101 – 112 ] …”
Section: Methodsmentioning
confidence: 99%